FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KENAKALAN REMAJA DI SMA SE KECAMATAN BUKIT RAYA PEKANBARU - LPPM Al-Insyirah (STIKes Al-Insyirah Pekanbaru, 2016)
Misbehavior Teenagers the act of deviating done by a teenager who can disadvantage himself or is people as kebut-kebutaan taking place, discard its common cutting class, and inconsiderate taking place raya.Based on the data from the agency permasyarakatan city pekanbaru 2015 there are 47 the convicts of them are teenagers.From 47 the prisoners, they are teenagers who resides in pekanbaru in the highway.General-purpose in this research is to find out the factors associated with mischief teenagers in sma sekecamatan the highway pekanbaru 2015. The kind of research this is research analytic quantitative by using design Cross Sectional Study. The population in this research was all other students class x and xi n 14 senior high school, YLPI high school, sma pgri and senior high schools widya graha that is as many as 882 people .Samples for this penelitin 153 people and techniques of the sample collection is Stratifed Random Sampling. The analysis used is univariat analysis and bivariat by test chi-square, a measuring instrument that is used is the questionnaire and data processing using computerized. The results of research shows that there are the relationship between a family with misbehavior arenas (P 0.011 value, POR = 2,489, CI=1,275-4,861), the mass media (P 0.033 value, POR = 2,162, CI=1,116-4,187), their peers (P 0.004 value, POR = 2,852, CI=1,436-5,603) with juvenile delinquency.And there was no correlation between the community (P value 0.234) with misbehavior teen ages.